Analysis Of The Influence Of Economic Growth, Education, Unemployment Rate And Wages In Reducing The Number Of Poor People In Medan City In 2013 – 2022 - Bella Meilysa; Rahmad Sembiring (International Journal of Management, Economic and Accounting, 2025)
The city of Medan, as one of the major cities in Indonesia, faces complex challenges related to poverty that have a wide impact on the economy and society of the community. This study aims to analyze economic factors that affect poverty in Medan City, especially the variables of economic growth, education, unemployment rate, and wages during the 2013-2022 period. The method used is multiple linear regression, to measure the simultaneous and partial influence of these variables on poverty levels. The results of the study show that simultaneously, these variables have a significant effect on poverty. However, partially, only wages have a significant influence, while economic growth, unemployment, and education do not directly affect poverty. Increasing wages is a key factor in reducing the poverty rate in Medan City.